Inflammatory Myofibroblastic Tumor of the Bladder: 2 Rare Cases Managed with Laparoscopic Partial Cystectomy - Sofia Santos Lopes; Andrea Furtado; Rita Oliveira; Ana Cebola; Bruno Graça; Manuel Ferreira Coelho; Fernando Ferrito; Carrasquinho Gomes (Case Reports in Urology)
Two cases of inflammatory myofibroblastic tumor (IMT) of the bladder are reported here. Both patients were male and presented with macroscopic hematuria; in the first case terminal hematuria was associated with irritative voiding symptoms. The second case was a smoker with hematuria unresponsive to medical treatment and anemia. Clinical presentation, pathological features, treatment, and prognosis are discussed. Due to rarity of this pathological condition, there are no guidelines concerning treatment and follow-up. We present our follow-up scheme and highlight the use of laparoscopic partial cystectomy as a successful treatment approach.